Histomorphometry of human vermiform appendix - Aggarwal, Meenakshi; Vohra, Hitant; Singh, Poonam (International Journal of Research in Medical Sciences, 2019)
Background: Acute Appendicitis is one of the most common acute abdominal conditions. Advances in modern radiographic imaging have improved diagnostic accuracy, however the diagnosis of appendicitis remains essentially an enigmatic challenege. Though much work has been done on morphometry but there is less work done on variation of histomorphometric features of appendix. Hence the study was carried out by keeping the following objectives in mind. Aim was to study the general histomorphology and measure the histomorphometric parameters of human vermiform appendix. And also, to study diagnostic significance of histomorphology and histomorphometric parameters in causing appendicitis. Methods: The study was conducted in the Department of Anatomy. Specimens of appendix were obtained from embalmed cadavers. Serial sections were taken at different levels and slides were prepared. The slides were then examined using Nikon Trinocular Research microscope under magnification power of 40x for various parameters, after staining with H&E. Results: The mean luminal diameter varied from 1.32±0.65mm at base to 1.22±0.72mm from base. Diffuse lymphatic tissue was seen in both mucosa and sub-mucosa. Conclusions: Definitely there is a relationship between lymphoid follicle diameter and mucosal-serosal thickness on one hand and that between the luminal diameter and lymphoid follicle diameter on the other hand. Since our study was restricted to geriatric age group so studies need to be done in different age groups to highlight any further relationship.